Pôle de Compétitivité en Algérie: Cas du Pôle Agroalimentaire de Bejaia - Timeridjine, Sara; Chitti, Mohand (جامعة قاصدي مرباح - ورقلة, 2021)
The phenomenon of company concentration through the formation of clusters becomes an important issue for companies. The interest of these clusters is to be able to use all means and knowledge to promote innovation and increase competitiveness, based on the cooperation of all the players in the cluster. Thus, in this work, we want to highlight the importance of clusters and the experience of many developed and developing countries including Algeria specifically through Bejaia food cluster. The study of this cluster led us to deduce the non-existence of this last in the region, but nevertheless allowed the emergence of the drinking cluster.
Keywords: النشاط الاقتصادي -- القطاع الزراعي -- الأغذية الزراعية -- القدرة التنافسية -- الجزائر